2022
DOI: 10.15332/us.v21i2.2675
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome de agotamiento en profesionales de la salud posterior al primer año de pandemia por COVID-19

Abstract: Objetivo: Determinar el nivel de agotamiento profesional en personal sanitario, posterior al primer año de pandemia por Covid-19 Materiales y Métodos: Estudio observacional, descriptivo, transversal, con muestra de 355 trabajadores de IPS de la ciudad de Cartagena. Se empleó un cuestionario de dos secciones: Aspectos sociodemográficos y laborales (16 ítems) y Maslach Burnout Inventory que determina el síndrome de Burnout a través de las dimensiones de agotamiento emocional, despersonalización y baja real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Regarding the hospital area, our study identified that the professionals who work in ICU areas of hospitals have a higher prevalence of moderate BS, while personnel who work in outpatient and emergency departments have a higher prevalence of severe BS [ 47 , 48 ]. Other primary studies report that the prevalence of BS and its dimensions in professionals who work in emergency departments and ICU is high compared to that found in professionals who work in other areas [ 48 , 49 ]. Also, similar results are reported in other systematic reviews that include samples of emergency room nurses [ 4 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the hospital area, our study identified that the professionals who work in ICU areas of hospitals have a higher prevalence of moderate BS, while personnel who work in outpatient and emergency departments have a higher prevalence of severe BS [ 47 , 48 ]. Other primary studies report that the prevalence of BS and its dimensions in professionals who work in emergency departments and ICU is high compared to that found in professionals who work in other areas [ 48 , 49 ]. Also, similar results are reported in other systematic reviews that include samples of emergency room nurses [ 4 , 50 ].…”
Section: Discussionmentioning
confidence: 99%